A phase III double-blind placebo-controlled randomized study of dexamphetamine sulfate for fatigue in primary brain tumors patients: An ANOCEF trial (DXA). Issue 1 (10th November 2019) - Laigle-Donadey, Florence; Ducray, François; Boone, Matthieu; Diallo, Mamadou Hassimiou; Hajage, David; Ramirez, Carole; Chinot, Olivier; Ricard, Damien; Delattre, Jean-Yves
Abstract: Background: Most patients suffering from a primary brain tumor (PBT) complain of chronic fatigue affecting their quality of life (QOL). We hypothesized that dexamphetamine sulfate, a psychostimulant drug, could improve fatigue in PBT patients. Methods: A double-blind, phase III, multi-institutional, placebo-controlled randomized trial (1:1 allocation) assessed the efficacy and tolerability of dexamphetamine at a dosage of 30 mg/day in PBT patients with stable disease who complained of severe fatigue, defined as a Multidimensional Fatigue Inventory (MFI-20) score ≥60. The primary outcome was the variation of the MFI 20 score between inclusion and the evaluation at 3 months in nonprogressive patients. Mood, QOL and cognitive function were also evaluated. Results: From April 2013 to November 2016, 46 patients were enrolled in the study, 41 of whom were evaluable for analysis (dexamphetamine group: 22; placebo group: 19). Tolerance was generally good, with no treatment-related deaths and no grade 4 toxicity. Patients in the dexamphetamine arm complained more frequently of psychiatric side effects (mostly hyperactivity, anxiety, sleep disorder, and irritability) than patients in the placebo arm ( P  = .018). There were no statistically significant differences at 3 months between the dexamphetamine and placebo arms in any of the outcomes (MFI-20, Norris Visual Analog Scale, Hospital Anxiety and Depression Scale (HADS), QOL (EORTC QLQ-C30/BN 20), Marin's Apathy Evaluation Scale, and cognitive evaluations). Conclusion: Dexamphetamine at a dosage of up to 30 mg/day for 3 months has acceptable tolerability in PBT patients but does not improve fatigue, cognitive function, or QOL.